Optimalisasi Pengelolaan Data Material PT Berkah Anugerah Inti Semesta Melalui Pengembangan Dashboard Inventory dengan Tableau - Ubaidillah; Rusindiyanto (Jurnal Serambi Engineering, 2025)
Optimal inventory management is essential for companies to ensure that materials are available when needed and to reduce the risk of shortages or overstocking. PT Berkah Anugerah Inti Semesta faces challenges in managing inventory data optimally. This study aims to develop an inventory dashboard using Tableau as a data visualisation tool for the company's inventory management. The research method uses the ETL process to process inventory data from different sources. The processed data is then visualised into an interactive dashboard that displays information about the company's materials. The research results show a summary through the dashboard with a total of 4,119 incoming materials, 3,648 outgoing materials and 471 remaining units. Monthly trends show that activity peaks in August-September. The material with the highest turnover rate is SIKU 50MM X 6M. This inventory dashboard provides an effective solution for improving the efficiency of the company's inventory management. The study recommends the integration of real-time data and predictive analysis for further development.